Faktor-Faktor Penyebab Kerusakan Koleksi Tercetak di Dinas Kearsipan dan Perpustakaan Kabupaten Boyolali - Intan Enjie Saputri; Nurlistiani (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Introduction. Printed collections are among the most vulnerable types of library materials, requiring appropriate preservation measures to maintain their physical condition and information value. This study aims to identify the factors causing damage to printed collections and to examine the prevention and repair efforts implemented at the Archives and Library Department of Boyolali Regency. Data Collection Methods. This study employed a descriptive qualitative approach. Data were collected through observations, semi-structured interviews, and documentation involving librarians responsible for collection preservation and management. Data Analysis. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing/verification. Results and Discussion. The findings indicate that damage to printed collections is caused by both internal and external factors. Internal factors include the quality of paper and adhesive materials, while external factors consist of environmental conditions, such as light exposure, temperature, humidity, dust, biological agents, and human factors related to library users. Prevention efforts include installing window films and curtains, maintaining room temperature at 20°C during service hours, routinely cleaning dust from collections, arranging adequate shelving space, applying insect-repellent chalk, displaying library regulations, providing a designated book return box, and installing fire sprinkler systems. Collection repair is conducted independently by librarians by classifying the damage into three categories: minor, moderate, and severe. Conclusion. The study concludes that preserving printed collections requires an integrated approach combining preventive preservation and corrective actions. Continuous environmental control, user awareness, and systematic repair procedures are essential to extend the lifespan of printed collections and ensure sustainable access to library information resources.